2019
DOI: 10.1587/transinf.2018edp7243
|View full text |Cite
|
Sign up to set email alerts
|

Improved LDA Model for Credibility Evaluation of Online Product Reviews

Abstract: When individuals make a purchase from online sources, they may lack first-hand knowledge of the product. In such cases, they will judge the quality of the item by the reviews other consumers have posted. Therefore, it is significant to determine whether comments about a product are credible. Most often, conventional research on comment credibility has employed supervised machine learning methods, which have the disadvantage of needing large quantities of training data. This paper proposes an unsupervised metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The experiments showed that this approach outperformed the existing methods in sales rank prediction based on online product reviews. In addition, Wang et al [ 15 ] proposed an unsupervised method for judging comment credibility based on the Biterm Sentiment Latent Dirichlet Allocation (BS-LDA) model. Their experimental results using comments from Amazon.com demonstrated that the overall performance of their approach could play an important role in determining the credibility of comments in some situation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experiments showed that this approach outperformed the existing methods in sales rank prediction based on online product reviews. In addition, Wang et al [ 15 ] proposed an unsupervised method for judging comment credibility based on the Biterm Sentiment Latent Dirichlet Allocation (BS-LDA) model. Their experimental results using comments from Amazon.com demonstrated that the overall performance of their approach could play an important role in determining the credibility of comments in some situation.…”
Section: Literature Reviewmentioning
confidence: 99%